Sagot :
Développer
(2a+1)²= (2a)² + 2*2a*1 + 1² = 4a² + 4a + 1
(7+b)(7-b)= 7² - b²
(a-√5)(a+√5)= a² - V5² = a²-5
(2x²-3)²=(2x)² - 2*2x*3 + 3² = 4x² - 12x + 9
(x²-1)(x²+1)(x⁴+1) = (x⁴-1²) (x⁴+1²) = x⁸ - 1
puisque tu sais par coeur que
(a+b)² = a²+2ab+b²
que (a-b)² = a²-2ab+b²
et que (a+b)(a-b) = a²-b²
simple application directe ici
Réponse:
(2a + 1)² = (2a)² + 2×2a×1 + 1² = 4a² + 4a + 1
(7+b)(7-b) = 7² - b²
(a-√5)(a+√5) = a² - (√5)² = a² - 5
(2x² - 3)² = (2x²)² - 2×2x×3 + 3² = 2x⁴ - 12x + 9
Voilà pour les réponses, j'espère que ça peut t'aider.